BIOLOGICAL YIELD CONTENT CORRELATED WITH YIELD COMPONENTS IN BARLEY (Hordeum vulgare L.) UNDER RAINFED CONDITIONS OF KURDISTAN- IRAQ - Asoz O. Abdullah; Nariman S. Ahmad; Kamil M. Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Barley is the second cereal crop grown after wheat in the Kurdistan region of Iraq. Low rainfall and high-temperature impact barley yields. A study investigating an F3 population of 100 segregated lines derived from a cross between Clipper, an Australian cultivar known for its high yield, and Local black, a cultivar recognized for its stress tolerance. The segregated F3 lines were assessed under two different environmental conditions at the Grdarash research station in Erbil and the Qlyasan research station in Sulaimani. The field trial data for the F3 population experienced analysis of variance and normality tests. Direct selection of high-yielding genotypes is challenging due to the complexity of the trait. Despite significant differences in yield among genotypes from various sources, genotypes showed no significant differences in harvest index (HI%). Location had a greater impact on yield-related traits of the segregated individuals, with temperature being a major influencing factor In Erbil, biological yield (BY) was significantly correlated with yield and its components, except for 1000-grain weight. In Sulaimani, BY was also significantly associated with yield and components, negatively correlated to HI%. Genetic effects were significant for BY but not HI%, with a negative genetic correlation between BY and HI% in Sulaimani. Significant impacts were observed on all attributes using regression analysis. except for 1000-grain weight, which had no significant correlation with BY or other traits. Biplot analysis indicated significant positive correlations between BY and yield-related traits, except for a negative %HI but insignificant correlation with 1000-grain weight.